Initiatives to Prolong Aging Assets Life Cycle: A Case Study in Royal Malaysian Navy - M. Halizahari; Mustakim Melan (International Journal of Supply Chain Management, 2016)
The research represents a case study on Royal Malaysian Navy (RMN) assets. Most of the assets are aging and were used more than its useful and economical life. The study demonstrates on initiatives used in maintaining and prolongs the life of aging assets in RMN. The asset life cycle stages were elaborates to allow the research of this area. The paper is based on review of literature and RMN experiences in managing aging assets. In additions, the study identifies new way of maintaining the assets for longer period without replacement. The paper also reveals that by applying these initiatives, RMN assets performance has increased and are able to be used extensively. The authors have recommended these initiatives to be the guidelines in the military and other sectors especially for logistics and transports industry in future.